PENGUKURAN KEPUASAN DAN KUALITAS PELAYANAN TERHADAP KONSUMEN JASA KULINER MIE GACOAN (STUDI KASUS PADA MIE GACOAN AREA SURAKARTA) - Oktavia Wulandari; Anton Agus Setyawan (MANAJEMEN DEWANTARA, 2024)
This research aims to look at the mediating role of service quality in the relationship between consumer service orientation behavior and physical facilities with Mie Gacoan consumer satisfaction in Surakarta. The research respondents were students at Muhammadiyah University of Surakarta who had made purchases at Mie Gacoan in Surakarta region. Data is collected through questionnaires and will be processed using PLS-SEM techniques using SmartPLS. The results conclude that consumer service orientation behavior and physical facilities have a positive and significant effect on the quality of culinary service consumer service in the Surakarta area. Meanwhile, service quality has a positive and significant effect on consumer satisfaction of Mie Gacoan in the Surakarta region